Problem-solving skills of futsal players with regard to some socio-demographic variables - Musa Con; Soner Cankaya; Mehmet Yalcin Tasmekteplıgıl; Kürşat Acar (Türk Spor ve Egzersiz Dergisi)
The aim of this study is to evaluate problem-solving skills of female futsal teams that compete in the Futsal League of Turkish Universities Sports Federation in terms of some socio-demographic variables. In total, 144 students from female futsal teams of 10 universities competing in the Futsal League of Turkish Universities Sports Federation voluntarily took part in this study. In the study, “Problem-Solving Inventory” that was developed by Heppner amp; Petersen was used. With this inventory, such sub-dimensions of the participants as “reliance on problem-solving skill”, “approach-avoidance” and “self-control” were analysed. In the statistical analysis of the obtained data during the research study, differences have been revealed by using one-way analysis of variance (One-Way ANOVA). And in the comparison of the averages of groups, Tukey HSD multiple comparison test was used. Research findings revealed that there are statistically significant differences between the points gained from the sub-dimensions of “reliance on problem-solving skill” and “approach-avoidance” with respect to the participants’ sporting age and the attended school; “reliance on problem-solving skill” with regard to father’s educational background; “approach-avoidance” with respect to income level (P lt;0.05). As a result, it is understood that such variables as sporting age, father’s educational background, income level and the attended university have important effects on individuals, and it is seen that individual’s level of solving problems increases as the sporting age increases. Within this scope, individuals are advised to start doing sports at early ages in order for them to develop their problem-solving skills.